REGIONAL WATER USE PRACTICES IN THE KWAHU EAST DISTRICT OF GHANA AND THE POTENTIAL INFLUENCE ON DIARRHEAL DISEASE - Lardner, Deborah; Passafaro, Michael; Gotimer, Kristin F.; Guernsey, David; Padgett, Christina; Sundar, Sriniketh (European Scientific Journal, ESJ, 2015)
Background: In low income countries, the Daily Adjusted Life Years (DALYs) of unsafe water, sanitation, and hygiene is 530/100,000 and is the 6th leading cause of death in children. Ghana, located in West Africa, is greatly impacted by poor sanitation and unsafe water supply. The objective of this study is to assess local water use and sanitation practices in the Kwahu East district of Ghana and how they relate to diarrheal disease. Methods: A cross-sectional survey was administered to 236 households in the Kwahu East district. It was divided into four sections: demographics, water use practices, water related illness, and water related sanitation. Prevalence data for certain variables were calculated and simple t-tests compared difference in water practices for different demographic groups based on gender, age, and education status. Results: Surface water and pump-well/borehole were the main sources of water for this area. Household demographics played a role in determining the household water collector. Over 95% of the responders did not treat their water. Moreover, gender, education, and age played significant roles in the degree of knowledge about diarrheal disease. Conclusions: Gender, education, age, and household size are all key factors that impact water practices. The results of this study can be used for the development of culturally sustainable interventions directed towards the improvement of access to safe drinking water, and in turn, reduce waterborne illness.